Athena: Speciality Certificate Examination case for Paediatrics and Genetics: a case of brittle hair. (1st July 2022) - Asfour, L.; Sinclair, R.
Abstract: Genetic hair disorders can be an isolated phenomenon or part of a multisystem syndrome. Microscopic examination of scalp hair can provide useful information to aid diagnosis. This article describes several hair‐shaft abnormalities, outlines genetic hair disorders with their associated genetic mutations, and clinical/hair phenotypes.